The influence of environmental cues on the activity of silver eels (Anguilla dieffenbachii) in Lake Manapouri, New Zealand. Issue 2 (3rd April 2019) - Stuart, Rose E.; Closs, Gerard P.; Lokman, P. Mark; Jellyman, Don
ABSTRACT: Lake Manapouri in the South Island of New Zealand has a significant hydroelectric generation facility, which potentially has a negative impact on the successful emigration of longfin eels ( Anguilla dieffenbachii ) from the upper Waiau catchment. Consequently, a trap-and-transfer programme has been implemented to allow silver (migratory) eels access to the sea. The present study analysed data on the timing of captures and numbers of silver eels over four seasons, including the influence of possible migration cues. Silver eels were captured over an extended season of seven months (November–May), with peak numbers during December and January. Flow at the lake outflow was found to have a weak relationship with the number of eels caught, as did lake level, but moon phase and rainfall had no significant effect. These results highlight the variability in silver longfin eel behaviour both in terms of timing and response to potential environmental cues.